Evaluasi Pengalaman Pelanggan Berdasarkan Metode Online Customer Service Experience (OCSE) Studi Pada Website Tokopedia - Febrian Pratama Putra; Yusi Tyroni Mursityo; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The purpose of this study is to empirically test a method used to measure customer experience that has been developed by previous studies. This is because most other studies that have been done only focuses on few factors of customer experience and not seeing customer experience in a broader way while companies have to innovate to survive in this competitive era. Online Customer Service Experience framework is used to measure the customer experience which will be evaluated in this study. This framework measures customer experience from psychology factors and the functionality of the website. This includes trust, value for money, context familiarity, usability, communication, product presence, social presence and interactivity. Interviewees used for this study is taken from 5 different person with different background to see customer experience in Tokopedia website from different perspective. This qualitative study uses interviews and observations from Tokopedia website to gather its data. Finding shows that majority of customer experience in Tokopedia is good based from trust, context familiarity, value for money, usability and communication. But few variables such as product presence, social presence and interactivity is still lacking and has to be improved since it affects purchasing intentions on their website.